ANALISA KEUNTUNGAN USAHA PETERNAKAN AYAM BROILER POLA MANDIRI DI KABUPATEN MALANG (Studi Kasus Di Kecamatan Karangploso Kabupaten Malang) - Murti, Ariani Trisna; Suroto, Karunia Setyowati; Karamina, Hidayati (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 1 (2020): Vol. 14 No. 1, 2020, 2020)
The study was conducted on several independent pattern broiler breeders in Karangploso District, Malang Regency, East Java Province. This type of research is quantitative research. The choice of location is based on the consideration that based on secondary data obtained from the Animal Husbandry and Animal Health Office of East Java Province, it is stated that Karangploso Subdistrict is one of the regions with the largest broiler population in Malang, amounting to 1,044,402 in 2018 (Malang Animal Husbandry, 2018). This aim of this research is to analyze the average amount of income and the amount of profit generated from independent pattern broiler chicken farming in Karangploso District, Malang Regency. Data collection was carried out in January 2019 - February 2019 with a purposive sampling method with criteria. The sample used is all independent breeders of broiler chicken with a total of 13 respondents. Quantitative analysis is calculated from total revenue, revenue, R / C ratio, BEP, ROI, and Payback Period (PBP). The results can be concluded that the independent pattern of broiler business in Karangploso District is feasible to be developed. The calculated value of the R / C ratio, BEP, and ROI is increasing from year to year. The average R / C ratio> 1, which is 1.07%. The average value of BEP, ROI, and PBP increased from 2016 to 2018, so that the independent broiler chicken breeding business can be declared profitable and feasible to be developed.